The Effectiveness of the Communication and Information Service Complaint Service in Absorbing the Aspirations of the Community in the Badung Regency Government Center - Nofita Eka Putri; Wirantari, I Dewa Ayu Putri (Socio-political Communication and Policy Review, 2026)
The complaint service managed by the Badung Regency Communication and Information Service is one of the important means in bridging communication between the community and the local government. This study aims to evaluate the effectiveness of these services in absorbing the aspirations of the community, by reviewing the aspects of accessibility, speed of response, and quality of follow-up to complaints. The research uses a descriptive qualitative approach through interviews and supporting documentation of complaint services. The results of the study show that complaint services have made a significant contribution to increasing public participation, although there are still obstacles such as delays in follow-up on certain complaints and lack of coordination between relevant agencies. These findings show that the complaint service is running quite effectively, but it requires strengthening the system and increasing the capacity of officers to be able to provide more optimal services.